Digitalization In The Role Of Budgetation In Increasing The Effectiveness Of Hospital Performance : DIGITALIZATION IN THE ROLE OF BUDGETATION IN INCREASING THE EFFECTIVENESS OF HOSPITAL PERFORMANCE - Yusri, Yusri; Novena Limena , Aurelia; Mauli Fatmala, Ella (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
Digitalization has helped hospitals improve the effectiveness of their performance in budgeting by collecting more accurate data, analyzing data for better projections, reducing operational costs, monitoring real-time budget usage, and facilitating better collaboration between departments. This paper aims to find out and understand the influence of budgeting on the effectiveness of hospital performance in the current era of digitalization. In this paper the author used a literature review method using library media, books and various electronic media sources which are currently developing rapidly. In this era of digitalization, it is important for hospitals to consider the use of information technology and financial management software for effective performance. By creating budgets that suit needs and monitoring market trends and performance, hospitals can achieve efficiencies and improve service quality. Accurate and effective budgeting is very important to improve hospital performance in the era of digitalization